2021
DOI: 10.3390/horticulturae7110496
|View full text |Cite
|
Sign up to set email alerts
|

Inferring the Potential Geographic Distribution and Reasons for the Endangered Status of the Tree Fern, Sphaeropteris lepifera, in Lingnan, China Using a Small Sample Size

Abstract: In this study, we investigated suitable habitats for the endangered tree fern, Sphaeropteris lepifera (J. Sm. ex Hook.) R.M. Tryon, based on fieldwork, ecological niche modeling, and regression approaches. We combined these data with the characterization of spore germination and gametophytic development in the laboratory to assess the reasons why S. lepifera is endangered and to propose a conservation strategy that focuses on suitable sites for reintroduction and accounts for the ecology and biphasic life cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Environmental factors, such as solar radiation and temperature, can affect mutation rates, metabolism and growth rates 58 . Previous studies have shown that cold temperature extremes, temperature stability over long- and short-terms, and the seasonality of precipitation were among the most important abiotic environmental factors affecting the distribution of S. lepifera 13 . Photosynthetic organisms generally have a much larger number of genes, usually 30,000, and many of these genes act in the photosynthetic leaf tissue 59 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Environmental factors, such as solar radiation and temperature, can affect mutation rates, metabolism and growth rates 58 . Previous studies have shown that cold temperature extremes, temperature stability over long- and short-terms, and the seasonality of precipitation were among the most important abiotic environmental factors affecting the distribution of S. lepifera 13 . Photosynthetic organisms generally have a much larger number of genes, usually 30,000, and many of these genes act in the photosynthetic leaf tissue 59 .…”
Section: Discussionmentioning
confidence: 98%
“…The capture and utilization efficiency of S. lepifera is higher than those of Alsophila spinulosa and A. podophylla 12 . Niche models indicate that extremely low temperatures, long-term and short-term temperature stability, and precipitation seasonality are important abiotic environmental factors affecting the distribution of S. lepifera 13 . After the leaves of S. lepifera fall, toxic substances such as p -coumaric acid and (-)-3-hydroxy- β -ionone can be decomposed and released to inhibit the growth of other woody plants in tropical forests 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Ultraviolet radiation can cause injuries to aboveground organs of organisms and limit their distribution (Wu et al., 2021 ). Tree ferns generally grow within light gaps in the canopy to avoid the effects of Ultraviolet (Wei et al., 2021 ). Of the five most important environmental factors, temperature annual range was a decisive factor (contribution rate of 44.9%).…”
Section: Discussionmentioning
confidence: 99%
“…Wei et al [9] investigated the characteristics of suitable habitats for the endangered tree fern, Sphaeropteris lepifera (J. Sm. ex Hook.)…”
Section: Dear Colleaguesmentioning
confidence: 99%